1995
DOI: 10.1007/bf01857707
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use and contraception in first sexual experiences

Abstract: Recent research has suggested that the use of alcohol or drugs in conjunction with sexual intercourse is associated with nonuse of contraception, particularly in first intercourse experiences. This paper reports findings from a nationally representative sample of adolescents and young adults aged 18-30 who were asked a number of questions about the circumstances and characteristics of the first time they had intercourse. Results showed that drinking at the time of first intercourse was more prevalent among tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…Although gender differences have been reported (e.g., Cooper and Orcutt, 1997), they have not been consistently observed across different behaviors or across different studies inves tigating the same behavior (e.g., Dermen and Cooper, 2000). Evidence on race differences is inconclusive because of the small number of studies that have included black youth and because few black adolescents and young adults drink in sexual situations Leigh et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Although gender differences have been reported (e.g., Cooper and Orcutt, 1997), they have not been consistently observed across different behaviors or across different studies inves tigating the same behavior (e.g., Dermen and Cooper, 2000). Evidence on race differences is inconclusive because of the small number of studies that have included black youth and because few black adolescents and young adults drink in sexual situations Leigh et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Coleman (2001a), however, in reviewing these studies, found inconsistency in their findings. Indeed, numerous studies of this nature, in contrast to the global correlation studies, failed to find an association between alcohol use and risky sex (e.g., Halpern-Flesher et al, 1996;Jacobson, Aldana, & Beaty, 1994;Leigh, Schafer, & Temple, 1995;Stall & Leigh, 1994;Temple, Leigh, & Schafer, 1993). In view of the evidence derived from event-specific studies, it is clearly presumptuous to argue that alcohol use, per se, always increases the likelihood of risky sexual behavior.…”
Section: Introductionmentioning
confidence: 94%
“…Alcohol use in adolescence is associated with the four leading causes of death within this age group: motor-vehicle crashes, other unintentional injuries, homicide and suicide; (CDC, 2004). Numerous studies have found that adolescent drinkers are at increased risk of engaging in violent and aggressive behaviors (DuRant et al, 1997; Grunbaum et al, 1998; White et al, 1999; Swahn et al, 2004), increased sexual activity and unsafe sexual practices (Graves and Leigh, 1995; Leigh et al, 1995; Duncan et al, 1999; Cooper, 2002) and sexual victimization (Kreiter et al, 1999; Champion et al, 2004). Adolescent alcohol use may also have deleterious effects on psycho-social development.…”
Section: Introductionmentioning
confidence: 99%